Imaging left‐ventricular mechanical activation in heart failure patients using cine DENSE MRI: Validation and implications for cardiac resynchronization therapy. Issue 3 (9th January 2017) - Auger, Daniel A.; Bilchick, Kenneth C.; Gonzalez, Jorge A.; Cui, Sophia X.; Holmes, Jeffrey W.; Kramer, Christopher M.; Salerno, Michael; Epstein, Frederick H.
Abstract : Purpose: To image late mechanical activation and identify effective left‐ventricular (LV) pacing sites for cardiac resynchronization therapy (CRT). There is variability in defining mechanical activation time, with some studies using the time to peak strain (TPS) and some using the time to the onset of circumferential shortening (TOS). We developed improved methods for imaging mechanical activation and evaluated them in heart failure (HF) patients undergoing CRT. Materials and Methods: We applied active contours to cine displacement encoding with stimulated echoes (DENSE) strain images to detect TOS. Six healthy volunteers underwent magnetic resonance imaging (MRI) at 1.5T, and 50 patients underwent pre‐CRT MRI (strain, scar, volumes) and echocardiography, assessment of the electrical activation time (Q‐LV) at the LV pacing site, and echocardiography assessment of LV reverse remodeling 6 months after CRT. TPS at the LV pacing site was also measured by DENSE. Results: The latest TOS was greater in HF patients vs. healthy subjects (112 ± 28 msec vs. 61 ± 7 msec, P  < 0.01). The correlation between TOS and Q‐LV was strong ( r  > 0.75; P  < 0.001) and better than between TPS and Q‐LV ( r  < 0.62; P  ≥ 0.006). Twenty‐three of 50 patients had the latest activating segment in a region other than the mid‐ventricular lateral wall, the most common site for the CRT LV lead. Using a multivariable model, TOS/QRS was significantly associated with LV reverse remodeling even after adjustment for overall dyssynchrony and scar ( P  < 0.05), whereas TPS was not ( P  = 0.49). Conclusion: Late activation by cine DENSE TOS analysis is associated with improved LV reverse remodeling with CRT and deserves further study as a tool to achieve optimal LV lead placement in CRT. Level of Evidence: 1 Technical Efficacy: Stage 1 J. MAGN. RESON. IMAGING 2017;46:887–896